UZBEK DIALECTS AND THEIR LEXICON - Mamatismoilova Hanifa (Western European Studies, 2025)
This article provides information about dialects and lacunae characteristic of peoples belonging to different ethnic groups who have lived in a certain territory since ancient times. At the same time, the specific features of dialects and areas, linguistic elements of ethnic groups, and ethnographic features are studied. At the same time, issues related to the ancient two major ethnic groups of modern Uzbeks - the Karluk and Kipchak dialects - according to the dialect features of the indigenous population of the region are also included
Keywords: ethnicity; lacuna; lexicon; dialect